The Effect of Intravascular and Extravascular Coagulation on Serum Fibrin Degradation Products in Rats - Van Stone, J. C; Khoury, N. Y (Thrombosis and Haemostasis, 1971)
Serum fibrin degradation products (FDP) were elevated following intravascular clotting in rats. The levels of these products were similar whether the blood clot remained localized in the inferior vena cava or embolized to the lung. The level of FDP increased with increasing amounts of blood clot formed. The intravascular injection of 100 u of thrombin induced high levels of FDP and resulted in death of the animals. Extravascular deposition of fibrin, either subcutaneously, intramuscularly or intraperitoneally had no effect on serum FDP.